Racism and Aboriginal Australian children’s wellbeing: impact and protective factors - Macedo, Davi Manzini (My University, 2020)
The present thesis explores the effects of racism on Aboriginal children’s social and emotional wellbeing (SEWB) and Aboriginal pregnant women’s mental health and wellbeing. Identification of protective factors against the effects of racism on child wellbeing was also contemplated. The thesis comprises seven chapters. Chapter 1 includes a review of the literature on characteristics of the Aboriginal Australian population and the effects of racism across the lifespan. This chapter also contemplates the Aboriginal Australian perspective on health and wellbeing and the role of ethnic-racial identity on Aboriginal Australian’s positive development. Chapter 2 describes the thesis’s aims and expected contributions. It describes the data sources in which the findings are based and the research questions explored. Chapters 3-6 include four peer-reviewed and published studies. The first study (chapter 3) is based on data from 369 Aboriginal pregnant women participating in the South Australian Aboriginal Birth Cohort Study. The findings show that racism is a pervasive experience, manifesting in the different settings (e.g., educational settings; public transport) in which Aboriginal pregnant women perform their daily activities. Racism was shown to be associated with increased stress and lower sense of personal control in this population. The next studies (chapters 4-6) were based on data from the Longitudinal Study of Indigenous Children (LSIC). Sample sizes varied according to the waves of the study included in the analyses. The second study (chapter 4) shows the effects of racism on Aboriginal children’s different social and emotional wellbeing (SEWB) domains. Risk ratios were calculated to estimate the effects on children’s emotional difficulties, peer problems, hyperactivity, conduct problems, and overall emotional and behavioural difficulties. The effect-measures indicated that the effects of racism on SEWB can be observed 1-2 years after exposure. In the third study (chapter 5), evidence was found for construct validity, reliability, criterion-validity, and measurement invariance by gender for a brief measure of Aboriginal children’s ethnic-racial identity (ERI) affirmation. These results provided evidence indicating the measure of ERI is valid, and it was then used in the subsequent study. The fourth study (chapter 6) showed that the effects of racism on SEWB was attenuated among Aboriginal children who had pronounced ERI affirmation. Implications for the protective role of ERI to different domains of SEWB were discussed. Finally, chapter 7 offers a summary of the overall findings and implication for this area of research. A list of references is provided within each chapter. The findings presented provide evidence of the impact of racism on Aboriginal pregnant women and Aboriginal children’s SEWB. Results from two modern cohorts indicated that Aboriginal pregnant women and Aboriginal children are subjected to racism in everyday settings, with associations between racism and poor SEWB and mental health. Evidence of validity and reliability was found for a measure of ERI affirmation in Aboriginal children. Furthermore, it was found that ERI affirmation might protect Aboriginal children against the impact of racism on SEWB. The findings show the effects of racism from a longitudinal perspective. The use of LSIC data is another strength, as LSIC is potentially the largest cohort study on determinants of Aboriginal children’s development and wellbeing. Future research can monitor the intergenerational effects of racism among Aboriginal Australians and the protective role of ERI affirmation across development.
Keywords: Health and wellbeing; Social engagement